Building a Space for the Human in IoT: Contributions of a design process - da Silva, José V.; Baranauskas, M. Cecília C.; Gonçalves, Diego Addan; dos Santos, Andressa Cristina (Journal of the Brazilian Computer Society, 2022)
Technological devices integrate people’s lives, actively connecting the Physical and the Digital worlds. Through ubiquitous computing, we can build a network of objects that, in addition to exchanging information, can perceive and act in a certain environment. The network of interconnected objects that is part of Human daily life can and should be called the Internet of Human Things (IoHT) as it involves re-configurations in living environments, in which objects (physical things) start to interact with each other and with people, often without human awareness. For this reason, the design of an IoT environment requires a good understanding of the problem and an evolution of ideas towards a possible solution in which People and other Physical things are linked to the Digital and can be considered as a single (Social, Physical and Digital) System. This article presents a Socially Aware Design process which evolves a solution starting from the understanding of the problem by the interested parties who act as co-designers. The process is illustrated with three workshops held with children, accompanied by their families in a hospital environment, whose objective was the evolution of an IoHT-based (Internet of Human Things) scenario. From the understanding of the design problem to the closing of the third workshop, the maturation of a design process for IoT environments with people is presented and discussed.